2020
DOI: 10.1371/journal.pone.0240587
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspectives on interventions to reduce stress in medical school: A qualitative study

Abstract: The mental health of medical students remains to be a matter of concern. Numerous setting-based and individual-based interventions for student mental health have been proposed in the literature. However, the student perspective on those interventions has been largely neglected. This study aims to explore how medical students perceive different interventions and if they desire any additional changes with regard to their studies. Eight focus groups with 71 participants were conducted at a large German medical sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…Students and faculty may have different perspectives on well-being and ways to promote it [ 22 ]. Nevertheless, students are capable of identifying their needs and specify their preferred programs, or even generate their own ideas for mental health programs [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students and faculty may have different perspectives on well-being and ways to promote it [ 22 ]. Nevertheless, students are capable of identifying their needs and specify their preferred programs, or even generate their own ideas for mental health programs [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Policy makers at all levels will eventually need to address the sources of distress in the education process itself if they wish to have a mental health program that is truly preventive [ 7 ]. A qualitative study that allowed students to generate their own ideas for well-being programs reported that students want changes to how their education is carried out [ 60 ]. Some suggested changes to the curriculum include pass/fail grading system, reducing contact hours, evaluating the depth of learning materials, and reformulating feedback given to students [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…By following an approach of data triangulation, the perspectives of students casting doubts on their studies and counsellors working with them could be taken into account to pursue our study aim. Analysis was performed in multiple rounds and by a multi-professional and experienced team of researchers (i.e., in terms of qualitative research with a focus on mental health among students [ 22 , 23 , 24 ]) to ensure intersubjective transparency.…”
Section: Discussionmentioning
confidence: 99%
“…was closely supervised by K.H. and A.L., who are both experienced in conducting and analysing qualitative interviews [ 22 , 23 , 24 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A hallgatók kritikája szerint a tananyag egy részének nincs klinikai jelentősége. Általános igény fogalmazódott meg arra, hogy ezt a tanítás és a vizsgák során is vegyék figyelembe, és határozzanak meg a tanulást segítő, egyértelmű kritériumokat (Dederichs, Weber, Muth, Angerer, & Loerbroks, 2020;Schiekirka és mtsai, 2012).…”
Section: Megbeszélésunclassified